Courtesy Stigma and Social Support: An Exploration of Fathers' Buffering Strategies and Blocking Rationalizations. Issue 13 (10th November 2019) - Tikkanen, Stephanie A.; Peterson, Brittany L.; Parsloe, Sarah M.
ABSTRACT: This study extends scholarship on stigma management communication and social support by exploring the experiences of fathers of children living with a rare health condition, Sturge-Weber Syndrome. Findings from this interview-based interpretive study reveal that fathers assuaged the negative effects of stigma on their children—and courtesy stigma on themselves—by employing buffering strategies, including reactive and preemptive information sharing, preparatory conversations, and support blocking. Further, fathers offered three rationalizations for their blocking behaviors—reasoning that to accept support would violate social norms, as well as privacy expectations and that accepting support was not worth the effort (social exchange). These findings encourage scholars to continue to upend predominant constructions of masculinity and also call to question prevailing assumptions about the relationship between technology and privacy.